2002
DOI: 10.1152/ajpheart.00920.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that NOS2 acts as a trigger and mediator of late preconditioning induced by acute systemic hypoxia

Abstract: Chronic systemic hypoxia (SH) enhances myocardial ischemic tolerance in mammals. We studied the delayed cardioprotection caused by acute SH and associated signaling mechanism. Conscious adult male mice were exposed to one or two cycles of hypoxia (H; 10% O(2)) or normoxia (21% O(2)) for various durations (30 min, 2 h, 4 h) followed by 24 h of reoxygenation. Hearts were isolated 24 h later and subjected to ischemia-reperfusion in a Langendorff model. Infarct size was reduced in mice pretreated with one (H4h) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 47 publications
2
58
1
1
Order By: Relevance
“…Similar to sublethal ischemia, hypoxia elicits PC-like response in which the myocardium develops an adaptive phenotype leading to resistance against subsequent lethal I/R injuries (Meerson et al, 1973;Bolli, 2000;Xi et al, 2002). This cardioprotection seems to be essentially mediated by hypoxia-inducible factor 1␣ (HIF-1␣) (Cai et al, 2003).…”
Section: Mirnas In Hypoxic Preconditioningmentioning
confidence: 99%
“…Similar to sublethal ischemia, hypoxia elicits PC-like response in which the myocardium develops an adaptive phenotype leading to resistance against subsequent lethal I/R injuries (Meerson et al, 1973;Bolli, 2000;Xi et al, 2002). This cardioprotection seems to be essentially mediated by hypoxia-inducible factor 1␣ (HIF-1␣) (Cai et al, 2003).…”
Section: Mirnas In Hypoxic Preconditioningmentioning
confidence: 99%
“…Hypoxic preconditioning (PC), like ischemic PC [9] can provide delayed protection against ischemia-reperfusion injury [10,11]. IH for 4 hrs with 10% O 2 induces cardioprotection illustrated by a reduction of infarct size in isolated rat heart [8].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of other stimuli, such as hypoxia, thermal stress, pharmacologic agents, and endogenous triggers of preconditioning such as nitric oxide and adenosine have also been shown to induce cardioprotective effects in several animal species (7)(8)(9)(10). Also, recent studies from our laboratory have shown that sildenafil citrate (Viagra), a selective PDE-5 inhibitor, induces powerful preconditioninglike protective effects in the ischemic heart (11).…”
mentioning
confidence: 99%